1965
DOI: 10.1063/1.1714074
|View full text |Cite
|
Sign up to set email alerts
|

Coercive Force of Single-Crystal GdIG as a Function of Temperature

Abstract: Intrinsic coercive force data for both single-crystal and polycrystalline gadolinium iron garnet (GdIG) are presented. Measurements near the magnetization compensation temperature (TCM) are stressed, and an explanation for the single peak in the intrinsic coercive force based on magnetization reversal by domain rotation rather than wall motion is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…For all the films, H C increases drastically as T Comp is approached and exhibits a sharp peak at T Comp , which is . [29] Another interesting fact is that at a fixed temperature, H C for the GSGG/GdIG(31 nm) film is more than twice of that for the GGG/GdIG(31 nm) film (see Figure S5, Supporting Information), which is consistent with a recent report on the strain-induced enhancement of H C in REIGs. [30] Radio frequency (RF) transverse susceptibility (TS) measurements were employed to determine the temperature evolution of the effective magnetic anisotropy for both IP and OOP configurations.…”
Section: Magnetization and Effective Magnetic Anisotropysupporting
confidence: 90%
See 1 more Smart Citation
“…For all the films, H C increases drastically as T Comp is approached and exhibits a sharp peak at T Comp , which is . [29] Another interesting fact is that at a fixed temperature, H C for the GSGG/GdIG(31 nm) film is more than twice of that for the GGG/GdIG(31 nm) film (see Figure S5, Supporting Information), which is consistent with a recent report on the strain-induced enhancement of H C in REIGs. [30] Radio frequency (RF) transverse susceptibility (TS) measurements were employed to determine the temperature evolution of the effective magnetic anisotropy for both IP and OOP configurations.…”
Section: Magnetization and Effective Magnetic Anisotropysupporting
confidence: 90%
“…For all the films, H C increases drastically as T Comp is approached and exhibits a sharp peak at T Comp , which is expected as H C for a compensated ferrimagnet like GdIG varies as 1|TTComp|. [ 29 ] Another interesting fact is that at a fixed temperature, H C for the GSGG/GdIG(31 nm) film is more than twice of that for the GGG/GdIG(31 nm) film (see Figure S5, Supporting Information), which is consistent with a recent report on the strain‐induced enhancement of H C in REIGs. [ 30 ]…”
Section: Resultsmentioning
confidence: 89%
“…The effect was explained by the diffusion of Gd 3+ and Ga 3+ ions into YIG films and hence may produce layers with compensation points. [31][32][33][34] In general, the post-deposition annealing treatment at 800 o C may cause moderate migration of Fe 3+ from the YIG film and Ga 3+ from the GGG substrate across the interface.…”
Section: Resultsmentioning
confidence: 99%
“…The problem remains a controversial subject. Whereas one study on Gd 3 Fe 5 O 12 showed that it exhibits a single peak in H c as a function of temperature [18], the others revealed a double peak in H c near T comp [19][20][21][22][23][24][25]. The key point is that previous researchers have not presented explicit magnetic behaviour (M-H) curves near T comp , which we will do in this paper.…”
Section: Introductionmentioning
confidence: 94%